Long-term inhalative sedation in children with pulmonary diseases - Meyburg, Jochen; Frommhold, David; Motsch, Johann; Kuß, Navina (Journal of intensive care medicine, 2021)
Objectives: To describe safety and feasibility of long-term inhalative sedation (LTIS) in children with severe respiratory diseases compared to patients with normal lung function with respect to recent studies that showed beneficial effects in adult patients with acute respiratory distress syndrome (ARDS). - Design: Single-center retrospective study. - Setting: 12-bed pediatric intensive care unit (PICU) in a tertiary-care academic medical center in Germany. - Patients: All patients treated in our PICU with LTIS using the AnaConDa® device between July 2011 and July 2019. - Measurements and Main Results: Thirty-seven courses of LTIS in 29 patients were analyzed. LTIS was feasible in both groups, but concomitant intravenous sedatives could be reduced more rapidly in children with lung diseases. Cardiocirculatory depression requiring vasopressors was observed in all patients. However, severe side effects only rarely occured. - Conclusions: In this largest cohort of children treated with LTIS reported so far, LTIS was feasible even in children with severely impaired lung function. From our data, a prospective trial on the use of LTIS in children with ARDS seems justified. However, a thorough monitoring of cardiocirculatory side effects is mandatory.
Online publiziert: 17. September 2020
Gesehen am 23.09.2025